A framework for computational fluid dynamic analyses of patient-specific stented coronary arteries from optical coherence tomography images. (September 2017) - Migliori, Susanna; Chiastra, Claudio; Bologna, Marco; Montin, Eros; Dubini, Gabriele; Aurigemma, Cristina; Fedele, Roberto; Burzotta, Francesco; Mainardi, Luca; Migliavacca, Francesco
Highlights: Development of a segmentation algorithm for automatic detection of lumen contours and stent struts from optical coherence tomography images. Validation of the automatic detection procedure against manual segmentation performed by expert image readers. Development of a reconstruction method, including alignment, rotation, and morphing operations, to obtain three-dimensional models of patient-specific stented coronary arteries. Validation of the three-dimensional reconstruction against measurements from X-ray computed micro tomography. Proof of feasibility of computational fluid dynamic simulations on realistic stented coronary artery models reconstructed from optical coherence tomography. Abstract: The clinical challenge of percutaneous coronary interventions (PCI) is highly dependent on the recognition of the coronary anatomy of each individual. The classic imaging modality used for PCI is angiography, but advanced imaging techniques that are routinely performed during PCI, like optical coherence tomography (OCT), may provide detailed knowledge of the pre-intervention vessel anatomy as well as the post-procedural assessment of the specific stent-to-vessel interactions. Computational fluid dynamics (CFD) is an emerging investigational tool in the setting of optimization of PCI results. In this study, an OCT-based reconstruction method was developed for the execution of CFD simulations of patient-specific coronary artery models which include the actual geometry of the implanted stent. The method was applied to a rigid phantom resembling a stented segment of the left anterior descending coronary artery. The segmentation algorithm was validated against manual segmentation. A strong correlation was found between automatic and manual segmentation of lumen in terms of area values. Similarity indices resulted >96% for the lumen segmentation and >77% for the stent strut segmentation. The 3D reconstruction achieved for the stented phantom was also assessed with the geometry provided by X-ray computed micro tomography scan, used as ground truth, and showed the incidence of distortion from catheter-based imaging techniques. The 3D reconstruction was successfully used to perform CFD analyses, demonstrating a great potential for patient-specific investigations. In conclusion, OCT may represent a reliable source for patient-specific CFD analyses which may be optimized using dedicated automatic segmentation algorithms.